2023
DOI: 10.1002/eco.2583
|View full text |Cite
|
Sign up to set email alerts
|

Application of a fish habitat model to assess habitat fragmentation using high flow and sediment transport in the Rumei Dam in Lancang River (China)

Ge Yang,
Meixia Bao,
Nan Cong
et al.

Abstract: Dam construction and operation can result in serious disturbances to the downstream flow regime and fluvial process, river morphology and the river's ecological condition worldwide. To understand the effects of discharge and sedimentation on fish habitats and ecosystems, an ecohydraulic approach was applied to one of the mega hydropower schemes in the downstream Lancang River (Tibet). The approach comprised a dam operation module with high flow and sediment transport and the application of a dynamic fish habit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…However, despite the social and economic benefits, water conservancy projects like reservoirs inevitably disrupt river connectivity, modifying hydrological conditions, including water level, flow, temperature, turbidity, and more [3][4][5]. These changes result in a decrease in the habitat suitability for fish, notably impacting the existing fish community structure and distribution within the watershed [6,7]. Preserving appropriate ecological flow and habitat conditions is a prerequisite for ensuring the reproduction of fish [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the social and economic benefits, water conservancy projects like reservoirs inevitably disrupt river connectivity, modifying hydrological conditions, including water level, flow, temperature, turbidity, and more [3][4][5]. These changes result in a decrease in the habitat suitability for fish, notably impacting the existing fish community structure and distribution within the watershed [6,7]. Preserving appropriate ecological flow and habitat conditions is a prerequisite for ensuring the reproduction of fish [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…However, the implementation of e-flows in regulated rivers has become increasingly powerful means to protect biodiversity and ecosystem services and to address multiple social, political and economic challenges of river basin management around the world. For instance, with e-flow guidance, the HHM has become very useful for evaluating the fragmented habitat of the two targeted fish species Schizothorax prenanti (S. prenanti) and Schizothorax davidi (S. davidi) in the downstream Lancang River (Tibet) under the dam operation module under high flow and sediment transport conditions (Yang et al, 2023). Wu et al (2024), on the other hand, assessed fringing vegetation conditions of the Hattah Lakes floodplain in south-east Australia by modelling the 32-year Landsat imagery data of the normalized difference vegetation index (NDVI) and environmental water allocations and natural floods and identified that the environmental water delivered 3 months prior to the Landsat image date is a crucial factor for better vegetation condition.…”
mentioning
confidence: 99%
“…However, in regulated river systems, the construction of barriers has greatly fragmented the habitats causing a significant biodiversity decline. Regulation has severely impeded movement of aquatic organisms, geomorphology and altered natural flow regimes (Sofi et al, 2023;Yang et al, 2023). However, the implementation of e-flows in regulated rivers has become increasingly powerful means to protect biodiversity and ecosystem services and to address multiple social, political and economic challenges of river basin management around the world.…”
mentioning
confidence: 99%